THE IMPACT OF COFFEE BIOACTIVE COMPOUNDS ON OBESITY: MECHANISMS AND CLINICAL PERSPECTIVES - Sylwia Bartolik,; Iwona Górnicka,; Aleksandra Pastuszek,; Radosław Pastuszek,; Magdalena Rosiewicz,; Anita Janda,; Marcin Durowicz,; Karolina Bieńkowska,; Jan Drzymała,; Urszula Kierepka, (International Journal of Innovative Technologies in Social Science, 2025)
Coffee is globally consumed and contains bioactive compounds such as caffeine and chlorogenic acids, which may have the potential to act on body weight mechanisms. This review will summarize the current evidence on the effects of coffee consumption on human obesity risk. Several observational studies have reported that an increase in coffee intake is associated with a decrease in BMI and waist circumference, especially in men. These changes may have been brought about by thermogenesis, fat oxidation, changes in appetite, glucose and lipid metabolism, and altered gut microbiota. However, these studies conflict with each other, possibly due to varying types of coffee, preparation methods, and population characteristics. Overall, moderate coffee intake appears to help indirectly in obesity prevention; yet, more studies assessing these effects and the mechanisms that can be involved are necessary.Aim of study: The given sources consider the potential interaction between coffee consumption and either the development or prevention of obesity from a human-oriented perspective. Emphasis is placed on how the bioactive compounds, particularly caffeine and chlorogenic acids, affect bodily parameters linked to weight regulation and fat metabolism, while a few of these physiological effects may relate to appetite and the metabolism of gut microbiota.Materials and methods: The review is based on a comprehensive analysis of current literature, including clinical trials and observational studies. PubMed and Google Scholar databases were consulted using keywords related to coffee, caffeine, chlorogenic acids, obesity, metabolism, appetite regulation, and gut microbiota to retrieve relevant articles.